Effect of acrylamide and fructose on some parameters related to metabolic syndrome in adult male rats: Faisal Ali Lateef Al-Agele and Khalisa Khadhim Khudiar - Khudiar, Khalisa Khadhim (The Iraqi Journal of Veterinary Medicine, 2016)
This study is designed to investigate the effect of acrylamide on some metabolic syndrome parameters in adult male rats relative to fructose. Forty adult male rats were randomly divided into four equal groups (ten rat/group) and treated for 60 days as follows: Control: Rats in this group were received distilled water orally, groups T1 and T2: rats of these groups were given orally 0.5 and 1mg/kg B.W acrylamide respectively. Animals in the fourth (T3) group were given 40% fructose in drinking water. Blood samples were collected by cardiac puncture technique at different periods 0, 30 and 60 day of the experiment for measuring serum concentration of the following parameters related to metabolic syndrome: Dyslipidemia (high density lipoprotein-cholesterol, and triacylglycerol), uric acid and glutathione. The result revealed that oral intubation of two concentration of acrylamide or exposure of rats to 40% fructose in drinking water caused disturbance in lipid metabolism manifested by triacylglycerolemia, lowered high density lipoprotein-cholesterol concentration, lowered serum uric acid and glutathione concentration with hyperuricemia. These functional changes were accompanied by structural changes in the kidney. Sections in rat's kidney showed renal damage manifested by desquamation and degeneration of epithelial cells of renal tubule as well as lymphocyte infiltration between renal tubules. The results of this study concluded that acrylamide succeeded to induce sever changes in parameters related to metabolic syndrome in rats as does the fructose (the well-known inducer of metabolic syndrome). According to the available literature it seems that this is the first study which showed the effect of acrylamide on some parameters related to metabolic syndrome.